INTEGRATED GAS-LIQUID SEPARATOR-REACTOR FOR DETERMINATION Sn(II) AT TRACE LEVELS IN SOLUTION - A. Sentosa Panggabean; M. Bachri Amran; Buchari Buchari; Subur P. Pasaribu (Indonesian Journal of Chemistry, 2010)
The determination of Sn(II) ion at trace levels using integrated gas-liquid separator-reactor with hydride generation-quartz furnace atomic absorption spectrophotometer (HG-QFAAS) has been done. This modified gas-liquid separator at various sizes was able to increase sensitivity in the determination of Sn(II) in solution. The acid reagent mixing techniques, sample and reductant optimally occurs in a coil reaction before they are going to the gas-liquid separators. The optimum conditions of parameter measurement in the determination of Sn ion with HG method are influenced by type and concentration of acid, and the concentration of reductant has been evaluated. This optimum parameters can increase of analytical performance simultantly, which is shown by detection limit 3.74 mg L-1 for 100 mL injection volume (3.74 pg Sn). The accuracy of measurement shown by the % recovery of the Sn determination in natural water sample at > 95%, indicate this technique is good to be applied for tin analysis at picogram level.